Performance evaluation of micropropulsion systems with the application of Active Debris Removal - Daykin-Iliopoulos,A; Desai,R (2014)
Recent micropropulsion developments have increased the operational capabilities of microsatellites (< 100 kg), to the point where they are being considered for demanding missions such as Active Debris Removal (ADR). This study examines the state-of-the-art micropropulsion options that can be applied to a microsatellite performing a range of orbital manoeuvres such as ADR. To this end a generic system architecture is used for this example scenario with ranging delta-v requirements. A variety of propulsion systems are sized accordingly, and the trade-offs between the differing propulsion technologies evaluated with respect to the power requirements, System-Specific Impulse , and technology readiness level (TRL), as well as a ‘newly defined’ volume driven System-Specific Impulse . It was shown that the high specific impulse (> 2000s) and consequent mass and volume savings of miniaturised Electric Propulsion (EP) systems, such as the miniature ion and colloid thrusters, results in optimal ISSP’s and ISSP’s for the ADR scenario examined. Moreover an in-depth combined quantitative and qualitative analysis identifies delta-v regions most suited to both EP and Chemical Propulsion (CP) systems, as well as highlighting the inherent differences in the varying technologies with respect to volume as well as mass.